Current Aspects for Searching and Returning Assets: Problems and Perspectives for Ukraine - P. S. Bilevskyi (Bulletin of Kharkiv National University of Internal Affairs)
Numerous acts of corruption by high-ranking officials and abuse of power over the past ten years have been accompanied by large-scale withdrawals of illegally obtained funds from Ukraine abroad. Therefore, the strategic goal of the government was to build an effective system for searching and returning illegally obtained assets.